Tracking performance in football - an example using goal scoring data - Moreira Silva, P.; Garganta, J.; Maia, J. A.; Santos, P. M. (The Open Sports Sciences Journal, 2012)
Performance analysis contribution to game understanding is a widely accepted premise among the broad community of team ball sports, including football. In the literature it is possible to find a considerable amount of crosssectional studies addressing performance evaluations over time. However, longitudinal studies aiming to evaluate the performance of the same participants (individual or teams) are scarce. Recognizing the interest to address this problem, the present paper focuses on the application of "tracking" with the purpose of characterizing performance behavior in football over eight different competitive periods (seasons). To this effect, the tracked performance indicator selected was the average number of goals scored per season on ten representative leagues of European football. Through the analysis of this variable, a detailed look at goal scoring tendencies is provided resorting to the explanation of different statistical procedures. Among these, Cohen's kappa (K) and Foulkes & Davies gama (y) were emphasized and interpreted as measures of individual and global tracking, respectively. With this example, the usefulness of tracking performance is highlighted, opening new perspectives to explore the field of team and individual performance analysis.